2016
DOI: 10.1177/1049732315617444
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size in Qualitative Interview Studies

Abstract: Sample sizes must be ascertained in qualitative studies like in quantitative studies but not by the same means. The prevailing concept for sample size in qualitative studies is "saturation." Saturation is closely tied to a specific methodology, and the term is inconsistently applied. We propose the concept "information power" to guide adequate sample size for qualitative studies. Information power indicates that the more information the sample holds, relevant for the actual study, the lower amount of participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

46
4,541
0
62

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 5,772 publications
(4,649 citation statements)
references
References 18 publications
46
4,541
0
62
Order By: Relevance
“…Two focus groups of eight participants were deemed to provide sufficient information power for an exploratory analysis, where the ambition was not to cover the entire array of phenomena, but to discern patterns relevant for the study aim [30]. After initial analysis, the two groups were found to provide similar information, hence no further data collection was made.…”
Section: Methodsmentioning
confidence: 99%
“…Two focus groups of eight participants were deemed to provide sufficient information power for an exploratory analysis, where the ambition was not to cover the entire array of phenomena, but to discern patterns relevant for the study aim [30]. After initial analysis, the two groups were found to provide similar information, hence no further data collection was made.…”
Section: Methodsmentioning
confidence: 99%
“…However, after 15 interviews, we did not receive any new information about the topic of interest. We therefore concluded that we had achieved saturation, and no more healers were included in the study [46]. …”
Section: Methodsmentioning
confidence: 99%
“…We wanted information from all the different healthcare professionals who worked in the healthcare service in the communities. However, after 32 interviews we did not gather any new information and decided to finish the inclusion process [43]. All interviews except two were conducted at the participants’ workplaces.…”
Section: Methodsmentioning
confidence: 99%